The Peri Pascha Attributed to Melito of Sardis: Setting, Purpose, Sources - Cohick, Lynn H. (Brown Judaic Studies, 2020)
This volume remains one of the only major studies of the Peri Pascha. The Peri Pascha was authored by Melito, the Christian bishop of Sardis in the second century CE, as a homily. It is notable for its early, extensive, and sharply anti-Judaic typological analysis of the paschal lamb described in Exodus 12. Cohick's study explores the purpose, sources, and especially the anti-Judaic elements of this homily.